Representasi Nilai – Nilai Karakter Masyarakat Minangkabau pada Film Surau dan Silek - Ayu Khairunnisa; Effiati Juliana Hasibuan; Novri Novri (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2021)
The title of this research is the Representation of the Value of Minangkabau Characters in the Film Surau and Silek.  This research is motivated by the unique principles of life of the Minangkabau people which make Islam the basis of Adat and Culture.  The Minangkabau tribe has a traditional principle of "basandi syara ', syara' basandi Kitabullah" the meaning of this principle is a tradition based on Islamic law and Islamic law is the Al-Qur'an. The writer is interested in studying the principles of the Minangkabau people through a Minang film entitled Surau and Silek.  This film combines two interrelated elements, namely Religion and Self-defense arts (silat). Religion as basis of life for the Minangkabau people, while self-defense arts (silat) is a culture of human creation.  This study uses the semiotic theory by Rolanda Barthes. Data collection techniques consist of two types, namely primary and secondary data, primary data is the writer's findings in analyzing the film "Surau and Silek", while secondary data is data obtained by researchers through interviews with two sources. This research uses qualitative methodology with descriptive analysis.  The results of this study prove that the principles of life of the Minangkabau Tradition "Basandi Syara 'Syara' Basandi Kitabullah" are still the life principles that the Minangkabau people continues to use until now. There are 76 scenes that represent the character values of the Minangkabau people and are dominated by scenes of the application of Islam as the guidance of life the Minangkabau people.